Pengaruh Sikap dan Norma Subyektif Terhadap Niat Membeli Produk Barik di Kampung Batik Laweyan Surakarta - Hartati, Dhian Putri; Nurtantiono, Andri (STIE Surakarta, 2015)
The purpose of this research is: 1) To determine the effect of simultaneously between attitude and subjective norm on the intention to buy the product as namely Kampung Batik Laweyan in Surakarta, 2) To determine the effect of partially between attitude and subjective norm on the intention to buy the product as namely Kampung Batik Laweyan in Surakarta. The analyze used in this research are: Multiple Regression Analysis, t test, F test, analysis Coefficient of Determination. Based on the analysis, it can be concluded: 1) Attitudes and Subjective Norms have significant effect on the intention to buy the product simultaneously as namely Kampung Batik Laweyan in Surakarta, 2) There is a partial effect between attitude and subjective norm on the intention to buy the product as namely Kampung Batik Laweyan in Surakarta. The advice given is: 1) The advice given is: 1) To the enterprises as namely Kampung Batik Laweyan in Surakarta, cultivated more attention to consumer attitudes and subjective norms that influence the intention to buy batik clothes. 2) To other researchers, is expected to incorporate other variables that affect the intention to buy batik products.2) To other researchers, is expected to incorporate other variables that affect the intention to buy batik products